The origin of dyspnea and its role in the reduction of exercise endurance in patients with rheumatoid arthritis - Mikhail Vasil'evich Sheyanov; V A Sulimov; Mikhail Vasilyevich Sheyanov; V A Sulimov (Научно-практическая ревматология)
Objective. To study the prevalence and origin of dyspnea in patients with rheumatoid arthritis (RA) and to specify its impact on exercise endurance (EE) and quality-of-life (QL) indices. Subjects and methods. One hundred and four patients with RA and 100 patients without RA and chronic respiratory diseases were examined. General clinical examination was performed; QL was estimated using the Saint George's Respiratory Questionnaire and the EQ-5D; spirometry, body plethysmography, estimation of pulmonary diffusion capacity, pulmonary multislice spiral computed tomography (MSCT), and echocardiography were made. Five patients with RA underwent cardiopulmonary testing on a graded exercise treadmill with gas analysis (ergospirometry). Results. Dyspnea during exercise was reported by 54 (52%) patients with RA and 9 (9%) control patients (p < 0.001). Dyspnea was more frequently detected and more significant in RA patients with other symptoms of respiratory organ lesions (cough, sputum discharge, chest pain on breathing and coughing), anemia, and emotional disorders of the anxious-depressive type. The degree of dyspnea correlated with DAS 28 scores (r = 0.33; p < 0.01). No correlation was found between lung function parameters and blood gas composition. Pulmonary MSCT in RA patients with dyspnea more frequently revealed signs of bronchiolitis and lesion of the lung as its interstitial fibrotic type. Conclusion. Dyspnea is a common symptom and an important factor in reducing EE and QL in patients with RA. Dyspnea in these patients has a multifactorial origin. Of importance in its occurrence are the involvement of the lung and bronchi in the pathological process irrespective of the lung function, as well as RA-associated factors (including anemia), and nosogenic emotional disorders (anxiety and/or depression).